Avian virology : current research and future trends - Samal, Siba K. (Caister Academic Press, 2019)
This comprehensive book provides a timely update on all of the most important avian viruses: avian influenza virus, infectious bronchitis virus, Newcastle disease virus, infectious bursal disease virus, chicken anemia virus, infectious laryngotracheitis virus, avian adenovirus, Marek's disease virus, avian reovirus, avian pox virus, avian leukosis virus, avian metapneumovirus, and avian paramyxoviruses. The chapters are written by internationally recognized experts from all over the world who have made seminal contributions to their respective field of avian virus research. Each chapter covers the current knowledge on the history, genome organisation, viral proteins, genetics, episootiology, pathogenesis, immunity, diagnosis, prevention and control, and future challenges of these viruses. The book closes with a fascinating chapter that reviews the recent advances in avian immune responses to viral infection.